Federal Distributive Politics and the Unequal Distribution of Violence: Argentine Provinces in Comparative Perspective. Issue 1 (April 2019) - González, Lucas; Cáceres, María Belén
Violence is unequally distributed across provinces. In Argentina, the least violent provinces have a murder rate similar to Sweden's. The most violent ones have a murder rate comparable to South Sudan's. What explains this unequal distribution of violence? This article claims that political turnover at the provincial level reduces the partisan control over police forces and challenges previous informal pacts, while being in the opposition to the president decreases the likelihood of receiving federal assistance to fight violence. When both conditions are met at the same time, crime is more likely to increase. The study examines these claims using difference-in-difference and regression analysis for panel data of the Argentine provinces between 2002 and 2015 and a case study of the province of Santa Fe (the most violent in the country). In the conclusions, it also explores the comparative implications for the discussion on the unequal distribution of violence in federal democracies.